Management of the Research Madrasah Program in Developing Student Achievement at MAN Pekalongan - Hanif, Ma’mun; Riyadi, Ridho; Ta’rifin, Ahmad; Safitri, Hani Hasnah; Albab, Ulul (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2025)
This article is presented from the research results which reveals the achievements of the Research Madrasah Program in developing student achievement at Pekalongan State Madrasah Aliyah (MAN Pekalongan) in terms of input, process, output, and outcome/alumni aspects. By using qualitative research methods and types of field research, as well as data collection techniques through observation, in-depth interviews, and documentation, the results of this research show that; 1) The Research Madrasa Program at MAN Pekalongan in its implementation has referred to the guidelines for managing research learning in madrasas established by the Director General of Education, Ministry of Religion of the Republic of Indonesia in 2019. 2) The research madrasa program at MAN Pekalongan can be seen from the student recruitment strategy (input). Second, the process of organizing research madrasas (process). Third, the number of students' academic and non-academic achievements (output). Fourth, the distribution of MAN Pekalongan alumni in various PTNs (outcome). MAN Pekalongan as a madrasah conducting research is supported by a conducive learning environment, adequate facilities, high integrity of educators/guides, and transparent and democratic governance so that the learning process runs effectively and results in high student achievement.